The Role of Multiliteracies in Enhancing the ESP Curriculum at Vocational High Schools - Asrifan, Andi; Oliveira de Barros Cardoso, Luís Miguel (FKIP Universitas Lampung, 2025)
The Role of Multiliteracies in Enhancing the ESP Curriculum at Vocational High Schools. Integrating multiliteracies in English for Specific Purposes (ESP) education presents both challenges and opportunities in vocational high schools in South Sulawesi. Objective: This study investigates the effect of multiliteracies on enhancing the ESP curriculum at vocational high schools in South Sulawesi. This study aims to assess how multiliteracies can enhance student engagement and language proficiency in vocational education, while also addressing the specific challenges of implementation in Indonesia's peripheral regions, with an emphasis on aligning digital competencies and regional socio-cultural contexts. Methods: A convergent parallel mixed-methods design was utilized. Quantitative data were collected through an ESP proficiency examination and a multiliteracy survey, which involved 100 students and 10 teachers. Qualitative data were obtained from teacher interviews, student focus groups, and document analysis. Inferential analysis employed statistical tools such as Pearson correlation, t-tests, chi-square tests, and Confirmatory Factor Analysis, whereas qualitative interpretation was facilitated through thematic coding using Nvivo software. Findings: The results indicate that 85% of students experienced increased engagement, while 75% demonstrated enhanced ESP performance after the integration of multiliteracies. Nonetheless, hardly 40% of teachers perceived themselves as sufficiently trained to execute these tactics. Essential qualitative observations highlighted the significance of culturally relevant content, including the incorporation of Bugis-Makassar maritime expertise, and the utilization of collaborative, multimodal resources. Teachers and students emphasized both the pedagogical advantages and the infrastructural and training constraints that impede full implementation. Conclusion: The integration of multiliteracies into the ESP curriculum shows significant promise for enhancing vocational language teaching in South Sulawesi. It enhances students' communicative skills and promotes participation through culturally relevant and technologically advanced content. Nonetheless, successful implementation necessitates focused teacher training, policy endorsement, and curriculum modification grounded in local values such as siri’ na pacce. Future studies should focus on the longitudinal effects and scalable professional development models within Indonesia's diverse educational environments. Keywords: multiliteracies, english for specific purposes (ESP), vocational education, student engagement, curriculum development.